Improvement of the separation device of the bead mill - Kozytskyi, Kyrylo; Osadchyi, Dmytro; Omelianenko, Kostiantyn; Hrininh-Hera, Kateryna (My University, 2025)
Innovative continuous bead mills needs the device for separating of suspension from the beads. The centrifugal bead separator is the most effective compared with a gap or cartridge separator.
Keywords: сепаратор відцентровий; бісерний млин; centrifugal separator; bead mill; кафедра мехатроніки та пакувальної техніки